2020
DOI: 10.1001/jama.2020.7869
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Postinfection Immunity

Abstract: This Viewpoint describes what is currently known about the immune response to coronavirus disease 2019 (COVID-19), highlights important gaps in knowledge, and identifies opportunities for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(103 citation statements)
references
References 11 publications
1
89
0
8
Order By: Relevance
“…A case of COVID-19 recurrence in a 48-year-old man was recently published [8]. As in the present case, the patient had anti-SARS-CoV-2 IgG, indicating that the acute phase of the disease and immunological reaction occurred, and suggesting that in some cases the presence of IgG antibodies could be not protective [8], although these suggestions should be taken with caution [9].…”
Section: Case Presentationmentioning
confidence: 44%
See 1 more Smart Citation
“…A case of COVID-19 recurrence in a 48-year-old man was recently published [8]. As in the present case, the patient had anti-SARS-CoV-2 IgG, indicating that the acute phase of the disease and immunological reaction occurred, and suggesting that in some cases the presence of IgG antibodies could be not protective [8], although these suggestions should be taken with caution [9].…”
Section: Case Presentationmentioning
confidence: 44%
“…At the same time, a control chest computed tomography showed improvement in bilateral patchy ground glass opacities ( Figure). [4][5][6]9]. Increasing age, male gender, hypertension and corticosteroid treatment, which we know are highly prevalent in older adults, were recently associated to delay in viral clearance [10].…”
Section: Case Presentationmentioning
confidence: 99%
“…Recovered individuals remained immune, in the absence of clear evidence about duration of protection. [41] For the base model reflecting the status quo situation of response efforts to date in Liberia, quarantine and isolation were undertaken by some of the individuals identified through contact tracing. The impact of contact tracing on transmission was modeled by having a subset of new infections immediately removed from the infectious population; that is, a percentage ( ) of presymptomatic individuals would undertake quarantine and remain isolated through recovery or death, either at home or in a hospital depending on severity of symptoms, due to contact tracing.…”
Section: Methodsmentioning
confidence: 99%
“…Short immunity periods are the case for seasonal human coronaviruses (Callow et al, 1990;Galanti and Shaman, 2020;Kissler et al, 2020). Although natural infection with SARS-CoV-2 can induce neutralizing antibodies in humans (Brouwer et al, 2020;Chi et al, 2020;Ju et al, 2020;Shi R. et al, 2020), we still do not know if the infection confers immunity to prevent reinfection and, if so, for what duration (Altmann and Boyton, 2020;Ibarrondo et al, 2020;Isho et al, 2020;Kirkcaldy et al, 2020;Long et al, 2020;Robbiani et al, 2020;Staines et al, 2020). Many cases that tested positive after once turning negative are currently considered as reactivation, long-term shedding, or detection of residual genetic material Mahase, 2020b;Xiao A. T. et al, 2020) although a few cases of possible reinfection have been reported (Bloomberg, 2020).…”
Section: Coronaviruses Including Sars-cov-2mentioning
confidence: 99%